Implementation of narcotics rehabilitation services in mandatory reporting receiving institutions in south kalimantan province: legal and institutional analysis - Utomo, Darmono Budi (International Journal of Law, Environment, and Natural Resources, 2026)
Drug abuse in Indonesia is a multidimensional problem affecting health, social, and legal aspects, addressed through a rehabilitative approach within the Mandatory Reporting Institutions system. This study aims to analyze the implementation of drug rehabilitation services in South Kalimantan Province, focusing on legal aspects, policy effectiveness, institutional conditions, and existing challenges. Using a normative-empirical (socio-legal) method with a legislative approach and field research at several institutions, the findings show that all Mandatory Reporting Recipient Institutions have strong legal standing and have implemented service standards based on Indonesian National Standard 8807:2022 Type III. These include mandatory reporting mechanisms, assessment procedures, treatment planning, referral systems, and service evaluation. However, policy implementation is considered fairly effective but not yet optimal, particularly in terms of system integration, human resource capacity, and social stigma. Institutionally, although these facilities are formally established, disparities remain in multidisciplinary human resources, infrastructure availability, and digital integration across sectors. Key obstacles include limited expertise, incomplete rehabilitation facilities, suboptimal reporting systems, and persistent community stigma toward rehabilitation services. In conclusion, while implementation generally aligns with the legal framework and operates adequately, further strengthening in integration, institutional capacity, and stigma reduction is necessary to achieve a more effective, holistic, and sustainable rehabilitation system.